Nitric Oxide–Soluble Guanylyl Cyclase–Cyclic GMP Signaling in the Striatum: New Targets for the Treatment of Parkinson's Disease? - West, Anthony R.; Tseng, Kuei Y. (Frontiers in Systems Neuroscience, 2011)
Striatal nitric oxide (NO)-producing interneurons play an important role in the regulation of corticostriatal synaptic transmission and motor behavior. Striatal NO synthesis is driven by concurrent activation of NMDA and dopamine (DA) D1 receptors. NO diffuses into the dendrites of medium-sized spiny neurons (MSNs) which contain high levels of NO receptors called soluble guanylyl cyclases (sGC). NO-mediated activation of sGC leads to the synthesis of the second messenger cGMP. In the intact striatum, transient elevations in intracellular cGMP primarily act to increase neuronal excitability and to facilitate glutamatergic corticostriatal transmission. NO-cGMP signaling also functionally opposes the inhibitory effects of DA D2 receptor activation on corticostriatal transmission. Not surprisingly, abnormal striatal NO-sGC-cGMP signaling becomes apparent following striatal DA depletion, an alteration thought to contribute to pathophysiological changes observed in basal ganglia circuits in Parkinson’s disease (PD). Here, we discuss recent developments in the field which have shed light on the role of NO-sGC-cGMP signaling pathways in basal ganglia dysfunction and motor symptoms associated with PD and L-DOPA-induced dyskinesias.